2020
DOI: 10.1016/j.ygyno.2019.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of perioperative red blood cell transfusion on postoperative recovery and long-term outcome in patients undergoing surgery for ovarian cancer: A propensity score-matched analysis

Abstract: • Transfusion was associated with increased cancer recurrence and mortality in ovarian cancer patients. • Transfusion was associated with higher postoperative complication rates and longer hospitalization stays. • Transfusion was associated with more postoperative fluctuations in systemic inflammatory markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…Additionally, rates of organ-space SSI, which are an imperfect marker and likely underestimate the incidence of anastomotic leak after bowel resection ( Rickles et al, 2013 ), were low overall, but were twice as likely to occur among patients who had bowel resection (1% vs 5%, p = 0.12). Recent studies have examined the impact of allogeneic red blood cell transfusion on recurrence and survival among patients undergoing surgery for ovarian cancer, with overall mixed results ( Zhang et al, 2020 , Hunsicker et al, 2019 , Pergialiotis et al, 2020 ). Given that our bowel resection cohort was much more likely to receive a blood transfusion (p < 0.01), consideration of this impact is warranted if transfusion of blood products is ultimately determined to be an independent predictor of worse recurrence and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, rates of organ-space SSI, which are an imperfect marker and likely underestimate the incidence of anastomotic leak after bowel resection ( Rickles et al, 2013 ), were low overall, but were twice as likely to occur among patients who had bowel resection (1% vs 5%, p = 0.12). Recent studies have examined the impact of allogeneic red blood cell transfusion on recurrence and survival among patients undergoing surgery for ovarian cancer, with overall mixed results ( Zhang et al, 2020 , Hunsicker et al, 2019 , Pergialiotis et al, 2020 ). Given that our bowel resection cohort was much more likely to receive a blood transfusion (p < 0.01), consideration of this impact is warranted if transfusion of blood products is ultimately determined to be an independent predictor of worse recurrence and survival.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the incidence of postoperative complications in patients receiving blood transfusion increased signi cantly during the perioperative period. Zhang et al reported that a perioperative blood transfusion potentially increases the risk of postoperative complications and is associated with a prolonged LOS (9). Furthermore, another study reported that perioperative blood transfusion may be associated with worse outcome in patients undergoing surgery(16).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies have found that the infusion of allogeneic blood inhibits the immune function of patients, which is not conducive to improving the prognosis in the perioperative period (9).…”
Section: Introductionmentioning
confidence: 99%
“…patients have an increased risk of developing infectious and non-infectious postoperative complications after major cancer surgery. [8][9][10] However, the results from a recent randomised controlled trial (RCT) demonstrate that a restrictive approach in which transfusions were triggered by haemoglobin (Hb) lower than 7 g/dL increased the risk of postoperative complications when compared with a liberal approach (Hb <9 g/dL). 11 Perioperative blood product transfusions may also impact long-term cancer outcomes (ie, recurrence and survival) by modulating the immune system, promoting inflammation and directly affecting cancer cells.…”
Section: Open Accessmentioning
confidence: 99%